Estabelecimento do capim-massai em consórcio com milho AG-1051 e Bt, em áreas infestadas pelo percevejo castanho das raízes. - Amaral, José Libério do; Costa, Ciniro [UNESP]; Fernandes, Luiza Maria de Souza; Medeiros, Mauro Osvaldo; Contri, Paulo César (My University, 2012)
The system consortium of grain crops with forage plants allows the establishment of pastures resistant, vigorous and lower cost in areas infested with stink bug brown root. Maize has favorable characteristics for intercropping as high plant height and insertion height of the studs, allowing the crop to occur without interference of forage plants. Furthermore, the production system in consortium with Bt corn reduced the infestation of Spodoptera frugiperda and was not affected by Scaptocoris carvalhoi (Hemiptera: Cydnidae), The Panicum maximum cv. Massai allowed a consortium with excellent corn and pasture provided a vigorous and excellent leaf mass distribution and very deep roots in the soil. Grain yield for Bt corn was higher and significant (P <0.05), compared to other treatments. The use of Lorsban (1.5 liters / ha) and Thiodan (2.0 liters / ha) was highly effective (P <0.05) in the control of Spodoptera frugiperda and Scaptocoris carvalhoi (Hemiptera: Cydnidae).

O sistema de consórcio de culturas de grãos com plantas forrageiras possibilita o estabelecimento de pastagens resistentes, vigorosas e menor custo em áreas infestadas pelo percevejo castanho das raízes. A cultura do milho possui características favoráveis para o cultivo consorciado, como alto porte das plantas e altura de inserção das espigas, permitindo que a colheita ocorra sem interferência das plantas forrageiras. Além disso, o sistema de produção em consórcio com a cultura do milho Bt, reduziu a infestação da Spodoptera frugiperda e não foi afetado pelo Scaptocoris carvalhoi ( Hemiptera: Cydnidae), O Panicum maximum cv. Massai permitiu um excelente consorcio com milho e proporcionou uma pastagem vigorosa e de excelente massa foliar e com distribuição muito profunda de raízes no solo. A produtividade de grãos pelo milho Bt, foi superior e significativa (P<0,05), em relação aos demais tratamentos. A utilização de Lorsban ( 1,5 Litros/ha ) e Thiodan (2,0 Litros/ ha ) foi altamente eficiente (P<0,05) no controle da Spodoptera frugiperda e Scaptocoris carvalhoi (Hemiptera: Cydnidae).
Establishment of grass in massai consortium with corn and ag- 1051 bt, in areas infested with stink brown roots
Keywords: Agriculture-Livestock Integration; Consorcio; Bt Corn; Panicum maximum; Insecticides; Pest Pastures; Integração Agricultura-Pecuária; Consorcio; Milho Bt; Panicum maximum; Inseticidas; Pragas de Pastagens